THE PROBLEM OF SELF-ANALYSIS AS A COMPONENT PERSONAL-PROFESSIONAL FORMATION STUDENT OF THE PEDAGOGICAL UNIVERSITY (Pedagogy of Higher and Secondary Education, 2007)
The article deals with the problem of self-directed analysis as a component of personal-and-professional growth of the student in Pedagogical University. Theoretical preconditions of the problem are defined.